Optimizing Islamic Boarding School Management in the Digital Era: Analysis of Technology Effectiveness in Administration and Operations - Tantowi, Ahmad; Gunawan, Muhammad Ali; Ibrahim, Abdullah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the application of technology in Islamic boarding school management and its impact on administrative efficiency and educational service quality. The findings reveal a significant positive effect of technology use using a phenomenological approach, in-depth interviews, and quantitative analysis with the Arellano-Bond and Blundell-Bond dynamic panel models. Technological implementation enhances administrative efficiency by improving data processing speed, recording accuracy, and information accessibility. Additionally, educational service quality improves, reflected in higher student and parent satisfaction, better learning outcomes, and enhanced interactions among administrators, teachers, students, and parents. Qualitative findings support these results, highlighting benefits such as easier student data management, equitable e-learning access, and more effective communication via instant messaging.  However, challenges include limited technology access, inadequate infrastructure, insufficient technological skills, resistance to change, funding constraints, and lack of government and community support. Policy recommendations include increasing government support for technological infrastructure, providing training programs, and fostering an adaptive organizational culture. This study offers a foundation for developing effective technology strategies in Islamic boarding schools, contributing to educational quality in the digital era. Further research should explore emerging technologies to enhance education.